New archaeobotanical evidence for Tolai hare (Lepus tolai) millets-consumption on the Loess Plateau of China. (April 2023) - Sheng, Pengfei; Liao, Jingwen; Allen, Edward; Sun, Zhouyong; Hu, Songmei; Guan, Ying; Shang, Xue
Highlights: Explores microbotanical remains preserved on ancient Tolai hare ( Lepus Tolai ) teeth from archaeological sites in late Neolithic China for the first time. Finds new archaeological evidence for Tolai hare dietary patterns in the context of the expansion of millet agricultural system on northern Loess Plateau at about 5000B.P. First discussion of the long-term interactions between humans and hare on the north Loess Plateau based on the multidisciplinary lines of evidence. Abstract: This study presents the results of a preliminary investigation on micro-botanical remains preserved on Tolai hare ( Lepus tolai ) teeth recovered from Yangjiesha, a site located on the north of the Loess Plateau in China, dated circa . 4900B.P. The microscopic analysis reveal that starch grains from Triticeae, millets and their wild relatives as well as wood tissue fragments were identified in dental residues This implies that, in the context of the intensive development of millet farming at about 5000B.P., hares at Yangjiesha may have been active inside or near the agricultural settlement areas and formed long-term interactions with humans against the new agricultural ecology of the north Loess Plateau.